Tannin-Based Natural Dye for DSSC: Polymerization Strategies to Maximize Efficiency - Hardeli; Ade Putri, Annisa; Gusmar Lina, Resi; Feronika, Widi; permatasari, Putri (Jurnal Kimia Riset, 2025)
Dye-sensitised solar cells (DSSCs) use dyes to absorb sunlight. Tannin is an eco-friendly natural dye alternative. However, the efficiency of tannin-based DSSCs is still low due to the limited number of conjugated double bonds. This study aims to improve the efficiency of DSSCs by polymerising tannin in two steps: Formaldehyde condensation under acidic conditions and glutaraldehyde crosslinking in alkaline medium. Parameter variations included initiator concentration (KOH vs. NaOH), crosslinking agent volume, polymerization time and temperature, and tannin monomer concentration. Characterization by FTIR and UV-Vis showed an increase in light absorption after polymerisation. The best results were obtained at 120°C, 2% NaOH initiator, 2.5 mL glutaraldehyde volume and 90 min reaction time, with DSSC efficiency reaching 9.18%, a fourfold increase compared to pure tannin (2.18%). This study shows that tannin polymerization significantly improves the efficiency of DSSCs, so it has the potential to be developed as a more efficient natural dye for photovoltaic applications.